Practical training report: Matu District Office, Matu Sarawak / Ainol Asyraf Rahim - Rahim, Ainol Asyraf (University Technology MARA Sarawak, 2019)
MATU DISTRICT OFFICE or also known as Pejabat Daerah Matu was established in 1991 whereas Matu was declared the 48th fall district on 5th May 1991. Before that, originally Matu was a small district in Sarikei's administrative division. However, it was only temporary because the Matu District administration was later placed under the Mukah Division Administration after Mukah was declared on 1st March 2002. Matu area is 677.28km. square covering the Small District of Igan which is the only small District under its administration. Matu District administrative area is around Pekan Matu. Igan up to Bungan, Sawai. Batang Lassa and Passin River. In general, Melanau are the majority residents of the Matu District as well as other races such as Malays, Iban, Chinese and others.